Preparation And Biological Properties Of PLA-MOF808 - Li, Yinglong; Liu, Yu (International dental journal, 2025)
Aim or purposeThis study aimed to fabricate a novel PLA-MOF808 composite scaffold using polylactic acid (PLA) as the base material with zirconium-based metal-organic framework (MOF808) loaded on both sides, and to evaluate its biocompatibility, osteogenic potential, and antibacterial properties for guided bone regeneration (GBR). Materials and methodsPLA fiber scaffolds were synthesized via melt electrospinning, with MOF808 grown in situ on the PLA surface to form PLA-MOF808. The scaffolds were characterized using scanning electron microscopy (SEM), water contact angle (WCA) measurement, tensile testing, and in vitro degradation assays. Biocompatibility was assessed via CCK-8 and cell adhesion assays. Osteogenic capacity was evaluated through alkaline phosphatase (ALP) staining, alizarin red staining, and qRT-PCR. Antibacterial efficacy against Escherichia coli and Staphylococcus aureus was determined via colony counting. ResultsThe PLA fiber scaffolds (diameter of 1.50 ± 0.36 μm), were successfully loaded with MOF808 to create the PLA-MOF808. PLA-MOF808 exhibited a WCA of 48.98° ± 5.60° (lower than PLA, p < 0.05), comparable tensile strength, and 10.01% mass loss after 28 days of degradation. Both scaffolds showed good biocompatibility, but PLA-MOF808 significantly enhanced osteogenic differentiation (p < 0.05), as evidenced by ALP, alizarin red, and qRT-PCR results. PLA-MOF808 exhibited excellent antibacterial properties, achieving an inhibition rate exceeding 90% against both Escherichia coli and Staphylococcus aureus. ConclusionsThe PLA-MOF808 scaffold, fabricated via melt electrospinning and in situ MOF808 growth, exhibited excellent biocompatibility, osteogenic capacity, and antibacterial effectiveness. These qualities make it a promising candidate for GBR applications.